2009
DOI: 10.4140/tcp.n.2009.299
|View full text |Cite
|
Sign up to set email alerts
|

<b>Screening for Undiagnosed Cognitive Impairment in Homebound Older Adults</b>

Abstract: Rates of undetected cognitive impairment are substantial in homebound elders receiving care from a visiting nurse service. The home health setting represents an important point in the continuum of geriatric care for detection of cognitive impairment. Future work should define the types and trajectories of cognitive impairment detected in home care patients by simple screens such as the Mini-Cog and test ways to integrate this knowledge into longitudinal treatment plans across settings of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Dementia, including Alzheimer’s disease, is the leading problem associated with being homebound, affecting 29% of the homebound population 17. A recent study showed that up to 17% of homebound elders have undiagnosed cognitive impairments 18. Our study showed that the homebound elderly had a high rate of cognitive impairment, especially in the memory and executive domains, which is associated with type 2 diabetes 19…”
Section: Psychiatric Disorders Of Homebound Elderlymentioning
confidence: 52%
“…Dementia, including Alzheimer’s disease, is the leading problem associated with being homebound, affecting 29% of the homebound population 17. A recent study showed that up to 17% of homebound elders have undiagnosed cognitive impairments 18. Our study showed that the homebound elderly had a high rate of cognitive impairment, especially in the memory and executive domains, which is associated with type 2 diabetes 19…”
Section: Psychiatric Disorders Of Homebound Elderlymentioning
confidence: 52%
“…This review provides evidence that pharmacy teams have provided services in a range of settings but few which incorporate community pharmacies. In addition to this, a large proportion of the studies included in this review were service evaluations, which leads to Collier [28] 2013 U Ireland Care/nursing home 54 U Conlon [46] 2009-10 U Ireland Care/nursing home 67 U Furniss [29] 2000 U a UK Care/nursing home 330 Hursh [47] 2008-09 U USA Care/nursing home~130 Kr€ oger [48] 2014 U Canada Care/nursing home 48 Maidment [49] 2011 U UK Care/nursing home 26 U Monette [50] 2004 U Canada Care/nursing home 90 Anderson [27] 2014 U USA Clinic 150 Nakamura [51] 2012-14 U Japan Clinic 35 Patel [52] 2010 U USA Clinic 20 U Sakakibara [53] 2014 U b Japan Clinic 50 Sonnett [23] 2012 U USA Clinic 302 Setter [54] 2004-5 U USA Community dwelling 100 Anonymous [22] 2014-15 U UK Community Pharmacy ? Breslow [25] 2013 U USA Community Pharmacy 26 Fountain [55] 2007 U USA Community Pharmacy 1 Manrai [26] 2015 U c UK Community Pharmacy ?…”
Section: Discussionmentioning
confidence: 99%
“…Anonymous [22] U e U Monette [50] Watanabe [21] U U Memory screening Breslow [25] U Rickles [24] U Setter [54] U Sonnett [23] Miscellaneous Anderson [27] U f Manrai [26] U g a Ap, antipsychotic; Ch, anticholinergic; Be, benzodiazepine. b…”
Section: Discussionmentioning
confidence: 99%
“…A study of 415 homebound older adults found that 29% had dementia (Kronish, Federman, Morrison, & Boal, 2006). When examining a sample of 100 older adult recipients of home care services with no prior history of cognitive impairment, it was found that 17% showed some level of cognitive impairment (Setter et al, 2009). This suggests that cognitive impairment is often not diagnosed in homebound older adults.…”
Section: Homebound Older Adultsmentioning
confidence: 99%
“…Screening for cognitive impairment is also an important part of this assessment process because it is the most prevalent psychiatric diagnosis in homebound older adults, and it can often be undetected in this population (Kronish et al, 2006;Setter et al, 2009).…”
Section: Delivery System Designmentioning
confidence: 99%